Pergerakan Relaps Pasca Perawatan Ortodontik - Tita Ratya Utari; Atiek Driana Rahmawati; Rohma Dwi Hartini (Fakultas Kedokteran Gigi UB, 2023)
Introduction: Orthodontic treatment is one of treatment in the field of dentistry by moving the teeth to correct malocclusion and malposition of the teeth. After treatment is complete, there is still the possibility of relapse, which is the process of moving the teeth to their original position before orthodontic treatment. It is still a complex problem after the end of orthodontic treatment. Objective: This literature review aims to examine the process and mechanism of relapse so that it can be additional information in efforts to prevent relapse. Discussion: Relapse can occur due to various factors and relapse occurs rapidly on day 1 to day 24 after removal of the orthodontic appliance. Orthodontic tooth movement and relapse movement will show an increase in the number of osteoclasts in areas of stress and a decrease in the number of osteoclasts in areas of tension. This suggests that alveolar bone remodeling is an important element in the process of relapse. Conclusion: Efforts to deal with relapse need to be carried out with various approaches, including pharmacologically which can affect the alveolar bone remodeling process, especially in osteoclast cells which play a role in the process of tooth relapse movement. Keywords: orthodontic treatment, tooth movement, relapse